Performance-Based Seismic Design of structural walls using a hysteretic multilinear model (2019)
In recent years, innovative structural systems based on Recycled Plastic Lumber walls (RPLW), precast ferrocement walls (PFW), and hollow reinforced concrete walls (HRCW) have been proposed for one and two-story housing so as to lessen the housing deficiency. This thesis presents the results drawn from cycling loading tests carried out over these three types of structural walls, in order to determine their strength, hysteretic behavior, ductility, energy dissipation capacity, equivalent viscous damping, and damage limit states. With the aim to assess their performances for the Design Basic Earthquake (DBE) and the Maximum Considered Earthquake (MCE), it was developed a nonlinear dynamic analysis methodology focused on the Performance-Based Seismic Design philosophy, which uses the Mostaghel’s multilinear hysteretic model to represent and describe accurately the actual inelastic behavior and energy dissipation capacity of the structural walls; for the parameter identification of this hysteretic model, a novel procedure that uses the simple Particle Swarm Optimization (PSO) algorithm was proposed, which estimated in a good way the experimental hysteretic behavior of the walls, so the models were good enough for simulation purposes. Additionally, the IO, LS, and CP structural performance levels were related to the damage limit states and several assumptions were made to obtain performance-based seismic assessments as realistic as possible. Also, sets of actual recorded and artificial ground motions were employed to validate the use of the methodology, which were scaled to achieve the spectral matching with the NSR-10 target spectrum. Using the median of the Incremental Dynamic Analysis (IDA) results, the performance points of the RPLW fell within the LS and CP ranges for the DBE and the MCE, respectively, which evidences that this structural system meets exactly the basic safety performance objective established in the design philosophy of the NSR-10 building code. On the other hand, the performance points of the PFW and HRCW fell within the IO range for both earthquake hazard levels, which demonstrates their excellent seismic behavior. The obtained results approve the use of these structural systems for one and two-story housing